Paraneoplastic hypercalcemia secondary to canine mammary tumors - Raposo-Ferreira, Talita Mariana Morata [UNESP]; Varallo, Giovanna Rossi [UNESP]; Calazans, Sabryna Gouveia; Jark, Paulo Cesar [UNESP]; da Cruz Lino Salvador, Rosana [UNESP]; Tinucci-Costa, Mirela [UNESP]; de Nardi, Andrigo Barboza [UNESP]; Cassali, Geovanni Dantas; Laufer-Amorim, Renée [UNESP] (Universidade Federal do Rio Grande do Sul, 2018)
Background: Paraneoplastic syndromes are complexes symptom that occur at a distinct site from the primary tumor or its metastasis by the production of hormone by the tissue in which the tumor appears. Paraneoplastic hypercalcemia is associated with an abnormal elevation of serum calcium levels and the mainly tumor related to this syndrome in canine is lymphoma, anal sac apocrine gland adenocarcinoma and multiple myeloma. In mammary tumors, the most frequent tumor that affect female dogs, this syndrome was also observed. The aims of this study were to evaluate serum calcium levels in female dogs with malignant mammary tumors and correlate calcium levels with clinicopathological parameters. Materials, Methods & Results: It was evaluated fifty-one female dogs with mammary carcinomas (simple carcinomas and carcinoma in mixed tumors) for serum calcium levels using colorimetric test. Clinical-histopathological data as spray status, pseudopregnancy, tumor size, ulceration, clinical staging, histopathological type and tumor grade were also evaluated in association with serum calcium levels. All dogs were treated with unilateral mastectomy. It was observed that 18 animals (35%) had calcium serum levels increased (>11.5 mg/dL) and 56% (10/18 cases) of these animals had serum calcium levels higher than 12 mg/dL. All dogs with hypercalcemia were asymptomatic, including two female dogs that presented the highest levels (13.43 mg/dL and 14.28 mg/dL). Hypercalcemia of malignancy was related to mammary carcinomas after the exclusion of other causes of hypercalcemia through laboratory tests (complete blood count and serum biochemistry) and abdominal ultrasound. No correlation was verified between the corrected serum calcium values with clinical and histopathological parameters evaluated. Discussion: In this study, it was observed a high incidence of paraneoplastic hypercalcemia associated with canine mammary tumors (35%). In humans, this syndrome is related in up to 10% of all patients with advanced cancer and with worse prognosis. The most frequent clinical signs of hypercalcemia are nonspecific and can be confused with other diseases, such as polyuria, polydipsia, anorexia, constipation, lethargy and weakness. The treatment of this syndrome is based on tumor resection and when necessary other treatments can be performed with fluid containing 0.9% sodium chloride, furosemide, prednisolone and calcitonin. Patients with asymptomatic or mildly symptomatic hypercalcemia (calcium levels <12 mg/ dL) do not require immediate treatment. Clinical signs occur more frequently with serum calcium levels higher than 15 mg/dL. Calcium levels higher than 18 mg/dL are considered a medical emergency and the clinical signs observed are trigger seizures, cardiac arrhythmia, acute renal failure and death. Most animals of this study presented mild hypercalcemia, that could justify the absence of clinical signs related to this syndrome, and the treatment for this syndrome was the tumor removal. The high serum calcium levels did not show correlation with more aggressive tumors and poorer prognosis, conditions evaluated by histological type, tumor grade and clinical stage. The evaluation of serum calcium levels is an important clinical test to be done in female dogs with mammary tumors, besides to be an affordable and technically simple test. The clinical signs related to this syndrome are nonspecific and may be confused with other diseases commonly observed in older dogs. The data suggest that there are no correlation between serum calcium levels with aggressiveness of canine mammary tumors and with other clinical features.
Keywords: Calcium; Carcinoma; Dog; Mammary gland; Paraneoplastic syndrome